Sialyl-Tn glycan epitope as a target for pancreatic cancer therapies - Abrantes, Rafaela; Lopes, Joanne; Lopes, Daniel; Gomes, Joana; Melo, Sónia A.; Reis, Celso A. (Frontiers in Oncology, 2024)
Pancreatic cancer (PC) is the sixth leading cause of cancer-related deaths worldwide, primarily due to late-stage diagnosis and limited treatment options. While novel biomarkers and immunotherapies are promising, further research into specific molecular targets is needed. Glycans, which are carbohydrate structures mainly found on cell surfaces, play crucial roles in health and disease. The Thomsen-Friedenreich-related carbohydrate antigen Sialyl-Tn (STn), a truncated O-glycan structure, is selectively expressed in epithelial tumors, including PC. In this study, we performed a comprehensive analysis of STn expression patterns in normal, premalignant, and malignant pancreatic lesions. Additionally, we analyzed the association between STn expression and various clinicopathological features. STn expression was statistically associated with pathological diagnosis; it was absent in normal pancreatic tissue but prevalent in pancreatic carcinoma lesions, including pancreatic ductal adenocarcinoma (PDAC), pancreatic acinar cell carcinoma, and pancreatic adenosquamous carcinoma. Moreover, we found a significant association between STn expression and tumor stage, with higher STn levels observed in stage II tumors compared to stage I. However, STn expression did not correlate with patient survival or outcomes. Furthermore, STn expression was assessed in PDAC patient-derived xenograft (PDX) models, revealing consistent STn levels throughout engraftment and tumor growth cycles. This finding supports the PDX model as a valuable tool for testing new anti-STn therapeutic strategies for PC in clinical setting.